UBUNTU AND ITS INFLUENCE ON LEADERS IN STRATEGY FORMULATION AND IMPLEMENTATION IN SOUTH AFRICA - Ngouessy-Guibinga, Gabriel Landry (My University, 2012)
Ubuntu Management Philosophy is believed to be the concept South African and other African organisations should adopt in order to sustain competitive advantage in the global market. The aim of this research is to assess to what degree Ubuntu influences South African leaders when formulating and implementing strategy. The study - which used a thematic type of analysis - shows that in two of the largest organisations in South Africa, the values of Ubuntu have started to strongly influence the manner in which their leaders formulate and implement strategy. The analysis has also shown that leaders of these organisations would recommend Ubuntu values to all South African and African organisations, in order to facilitate stronger economic growth. The success of Afro-renaissance is very important to African business people and academics. These individuals have the duty to educate and raise awareness amongst Africans, wherever they may be, and to urge them to integrate the values with their organisations and career paths. This process will help build a continent of hard working, caring, honest, non-racist and incorruptible people, and will stimulate economic growth and facilitate the fairer distribution of wealth in Africa.
MBA thesis - WBS
Keywords: Ubuntu; Strategy formulation; Strategy implementation